Analisis Dampak Kebijakan Restrukturisasi Kredit Terhadap Laba dan Likuiditas BPR di Kabupaten Badung - Ketut Tanti Kustina; I Gede Merta Nugrahita Suryawan; I Gusti Ayu Diah Utari (Universitas Warmadewa, 2022)
The purpose of this research was to determine whether or not there is an effect of OJK's credit restructuring policy on banks, which is reflected by a significant difference in profit and liquidity before and after the policy. Credit restructuring is a step to provide relief from bank loan installments or leasing loans for debtors or borrowers whose businesses and jobs have been directly or indirectly affected by the COVID-19 pandemic. This type of research is quantitative with the form of event study research and using the population of all BPRs in Bali Province. The research sample was taken using purposive sampling. The data analysis method used was a different test (paired sample t-test). The results of this study indicate that there is a significant difference in profits before and after the OJK credit restructuring policy, which means that the OJK credit restructuring policy as an effort to anticipate COVID-19 has a significant effect on banking.